Robust controller design for speed regulation of a flexible wind turbine - Ravikumar, N.V.A.; Saraswathi, G. (EAI Endorsed Transactions on Energy Web, 2019)
The complexity of large wind turbines increases due to fatigue, aerodynamics, structural flexibility and wind turbulence which lead to uncertainties in the wind turbine model. Hence, a robust controller is necessary to deal with these uncertainties. The uncertainties are represented in the wind turbine model by variations in the elements of the state space matrix comprising of mass, stiffness and damping elements. The generator speed is regulated with changes in the rotor collective blade pitch angle and disturbances in wind speeds. In this paper, we propose to design an H∞ controller which qualifies to regulate the generator speed of an uncertain wind turbine. The proposed H∞ controller demonstrates robust performance and stability on system with ±20% uncertainty. The obtained 14th order H∞ controller is reduced to 7th order by using a balanced truncation model order reduction method. The performances of the designed H∞ controller and the reduced controller are compared.
Keywords: Η∞ controller; model order reduction; robust stability; wind turbine